İşe Yabancılaşmanın İşgören Performansı Üzerindeki Etkisinde Yapay Zekâya Yönelik Tutumun Düzenleyici Rolü: Akademisyenler Üzerine Bir Araştırma (Üçüncü Sektör Sosyal Ekonomi Dergisi, 2026)
This study seeks to answer the research question: “How does attitude towards artificial intelligence shape the effects of work alienation on employee performance?”. Although the relationship between work alienation (WA) and employee performance (EP) is well established, limited research examines moderating conditions within digitalising work environments. In this respect, the research is based on the Affective Events Theory (AET). According to AET, events experienced in the workplace cause emotional reactions among employees. These reactions, in turn, influence employees’ attitudes and work behaviour. The AI-driven transformation of workplaces constitutes a significant development. In this context, the effects of GATAI on the workplace were examined. In view of the gap in the literature and the current developments, this study was conducted using data obtained from academics (N = 288) determined by convenience sampling. The results of the research model tested using the PROCESS Macro (Model 2) revealed that the negative impact of WA on EP is mitigated by a positive ATAI. This research examines the attitudinal perspective of AI and provides important insights for the workplace. It makes theoretical and empirical contributions to the literature.
Keywords: Duygusal Olaylar Teorisi; işe yabancılaşma; işgören performansı; yapay zekâ genel tutum; akademisyenler